Evidence in Lager Yeasts of β-Lyase Activity Breaking Down γ-GluCys-Conjugates More Efficiently Than Cys-Conjugates to Odorant Beer Polyfunctional Thiols - Romain Christiaens; Margaux Simon; Raphaël Robiette; Sonia Collin (Molecules)
The prevalence of glutathionylated (G-) precursors of polyfunctional thiols (PFTs) over their free forms has prompted investigating how to optimize the enzymatic breakdown of these precursors with yeast during lager, ale, and non-alcoholic/low-alcoholic beer (NABLAB) fermentation trials. Some Saccharomyces cerevisiae yeasts have been selected for their higher β-lyase activity on the cysteinylated (Cys-) conjugates (up to 0.54% for SafAleTM K-97), yet some S. pastorianus strains and one maltose-negative S. cerevisiae var. chevalieri yeast have proved to release PFTs more efficiently from G-precursors (up to 0.21% for BRAS-45 and 0.19% for SafBrewTM LA-01). The present study aimed to explore the possibility and extent of direct release in the beer of 3-sulfanylhexanol from its synthetic γ-glutamylcysteinylated (γ-GluCys-) precursor. Release efficiency was determined by GC-PFPD after the fermentation (7 days at 24 °C and 3 days at 4 °C) of a 15 °Plato (°P) wort enriched with 15 mg/L of synthesized γ-GluCys-3SHol. Up to a 0.28–0.35% release was measured with S. pastorianus strains BRAS-45 and SafLagerTM E-30, while much lower activities (≤0.16%) were observed with S. cerevisiae yeasts, including the maltose-negative chevalieri variety. This β-lyase activity on γ-GluCys-3SHol has never been described before. Under our experimental conditions, the efficiency of release from γ-GluCys-3SHol was drastically reduced in low-density worts. A strongly strain-dependent impact of temperature was also observed.